Effects of adapted physical education teacher preparation experiences on inclusion self-efficacy: a quanitative and qualitative study - Smith, Rachel L. (My University, 2013)
During teacher preparation, preservice teacher candidates undergo a variety of professional development opportunities that allow them to gain knowledge and experience that will be useful in the teaching field. Many physical education (PE) teacher preparation programs provide an introduction to adapted physical education (APE) survey course to prepare general PE teachers to instruct students with disabilities in the PK-12 setting. This study examined the effects of an introduction to APE course with an accompanying clinical experience on the self-efficacy towards inclusion of students with disabilities. Self-efficacy data were gathered from a group of students (N = 49) enrolled in an introductory APE course during the 2011 - 2012 academic year using the Situational-Specific Self-Efficacy and Inclusion of Students with Disabilities in Physical Education survey (Block, et al 2010). Further, a subgroup of these participants (n = 16) underwent a one-on-one interview to further examine aspects of the clinical experience that most influenced their self-efficacy. Survey results showed that the introductory course with clinical experience significantly improved self-efficacy among preservice teachers (p < .05). In addition, interviews revealed the combination of a lecture based course and the hands-on clinical experience were identified as the top two reasons why self-efficacy increased.
Keywords: Physical education for children with disabilities; Physical education teachers--Training of; Inclusive education